Characterizing the Core Internal Gene Pool of H9N2 Responsible for Continuous Reassortment With Other Influenza A Viruses - Yang, Haoyi; Hu, Mingda; Wang, Boqian; Jin, Yuan; Gong, Xingfei; Liang, Long; Yue, Junjie; Chen, Wei; Ren, Hongguang (Frontiers in Microbiology, 2021)
Reassortment among avian influenza viruses is the main source of novel avian influenza virus subtypes. Studies have shown that the H9N2 virus often donates internal segments to generate novel reassortant avian influenza viruses, acting as a reassortment template. However, the characteristics of the internal pattern of reassortment remain unclear. In this paper, we first defined the core gene pool of the internal segments of the H9N2 virus that provide templates for reassortment. We used genetic distance and sequence similarity to define typical clusters in the core gene pool. Then, we analyzed the phylogenetic relationships, feature vector distances, geographic distributions and mutation sites of strains related to the core gene pool. Strains in the same typical clusters have close phylogenetic relationships and feature vector distances. We also found that these typical clusters can be divided into three categories according to their main geographic distribution area. Furthermore, typical clusters in the same geographic area contain some common mutation patterns. Our results suggest that typical clusters in the core gene pool affect the reassortment events of the H9N2 virus in many respects, such as geographic distribution and amino acid mutation sites.